Polityka Stanów Zjednoczonych Ameryki wobec rozpadu Jugosławii w latach 1990-1991 - Szczesio, Sławomir (Acta Universitatis Lodziensis. Folia Historica, 2009)
George H. W. Bush became the President of the United States of America in January 1989. It was a very important moment in world’s history: the end of the cold war, the break-up of the Soviet Union and the Eastern block, and the war against Iraq in the Persian Gulf. But one of the troubles for the Bush administration, as well as for the governments of Europe, was the issue of Yugoslavia, where there were brewing many threats and problems, such as ethnic tensions, the rise of nationalism, conflict in Kosovo, and the economic crisis. When the cold war ended, Yugoslavia lost its geopolitical significance for the U.S. America further supported unity, independence, territorial integrity and the new Prime Minister Ante Markovid, but it was mainly rhetorical support. In June, 1991, Slovenia and Croatia declared independence, and war and collapse of Socialist Federal Republic of Yugoslavia began. For American diplomacy, this was an European issue and a test of European foreign policy. As James Baker put it, “We don't have a dog in this fight”. Furthermore, politicians in Europe claimed that, “this is the hour of Europe”. The United States played a second-rank role on Yugoslavia and supported the efforts of the European Union. But, in December, 1991, the E.U., under the influence of German diplomacy, ignored the protests of the U.S., the U.N. and international mediators, and decided to recognize Croatia and Slovenia. Yugoslavia had in fact collapsed, but soon there appeared a new problem for Europe and America – tensions in the subsequent Yugoslav republics, Bosnia and Herzegovina.